Georeferenced Micronutrient Status in Soils of Lakhimpur District of Assam - and Anjali Basumatari, Neelakshi Bhuyan, N.G. Barua, D.K. Borah, D. Bhattacharyya (Journal of the Indian Society of Soil Science, 2014)
An investigation was carried out to study the micronutrient status in soils of Lakhimpur district of Assam and their relationship with different physicochemical properties of soils. Two hundred seventy (270) georeferenced surface (0-0.15 m) soil samples were collected from Lakhimpur district using GPS. The soils of the Lakhimpur district varied from sandy to clayey. Sand, silt and clay content varied from 4 to 88, 4 to 68 and 4 to 68 per cent, respectively. Soils were strongly acidic to near neutral in reaction (pH 4.60-6.61) with organic carbon (oc) content ranging from low to high (1.20-18.3 g kg-1). The CEC ranged between 3.30 and 14.0 cmol(p+) kg-1. DTPA extractable Fe, Cu, Zn, Mn and HWS-B varied from 36.4 to 224.1, 0.10 to 5.40, 0.10 to 1.68, 4.60 to 131.3 and 0.10 to 0.92 mg kg-1., respectively. The soils of Lakhimpur district were sufficient in DTPA-Fe and DTPA-Mn, but deficient in DTPA-Zn (29.6%) and HWS-B (26.6%). Soil pH showed negative significant correlation with DTPA-Cu, DTPA-Fe, DTPA-Zn and DTPA-Mn. Soil CEC showed positive significant correlation with DTPA-extractable micronutrients except Mn, and OC showed positive significant correlation with HWS-B, DTPA-Cu, DTPA-Fe and DTPA-Mn. Regression analysis revealed that soil pH, OC, CEC and per cent clay were the main factors contributing 64.1 to 88.0 per cent of the variability in micronutrient contents in soil.